Indications, techniques, and outcomes of pit and fissure sealants in pediatric dentistry - Al Domyati, Roaa Mohammad; Saif, Nawaf Abdullah Al; Bogami, Baidha Bakheet Al; Zughaibi, Sarah Majid Al; Alkadi, Ahmed Mohammed; Alotibi, Turki Hassan; Alrashidi, Ahmed Abdullah; Alhazmi, Abdullah Hassan; Altasan, Mazin Abdullah; Alshemaisi, May Mohammed; Alamri, Fahad Mohammed (International Journal Of Community Medicine And Public Health, 2023)
Pit and fissure sealants are safe and effective preventive measures for reducing the risk of tooth decay in pediatric patients. The procedure for applying sealants is a relatively quick and non-invasive process that typically involves preparation, isolation, and etchant application. They are typically used on the occlusal surfaces of molars and premolars, which have deep grooves and fissures that are difficult to clean. Sealants are mostly applied to the permanent molars in children, as they are the most susceptible to decay due to their deep grooves and pits sealants are non-invasive, cost-effective, easy to apply, and long-lasting. However, sealants cannot be used on teeth with existing decay, and they may need to be reapplied periodically to ensure continued protection. Sealants are not a substitute for good oral hygiene habits, regular dental check-ups, and cleanings. The necessity of the preventive dental procedure is based on the child’s individual needs and the condition of their teeth.